Incidence of Bowel Surgery and Associated Risk Factors in Pediatric-Onset Crohn's Disease. Issue 12 (December 2016) - Rinawi, Firas; Assa, Amit; Hartman, Corina; Mozer Glassberg, Yael; Friedler, Vered Nachmias; Rosenbach, Yoram; Silbermintz, Ari; Zevit, Noam; Shamir, Raanan
Abstract : Background: Data describing the incidence and the risk factors for surgical interventions in pediatric Crohn's disease (CD) is inconsistent. Our aim was to describe the rates of intestinal surgery and to identify associated risk factors in a large cohort of children with CD. Methods: Medical charts of 482 children with CD from the Schneider Pediatric Inflammatory Bowel Disease cohort who were diagnosed between 1981 and 2013 were carefully reviewed retrospectively. Results: Of 482 patients, 143 (29.7%) underwent intestinal surgery with a median follow-up time of 8.6 years (range, 1–30.5). Kaplan–Meier survival estimates of the cumulative probability of CD-related intestinal surgery were 14.2% at 5 years and 24.5% at 10 years from diagnosis. Of these, 14% needed more than one operation. Multivariate Cox models showed that isolated ileal disease (hazard ratio [HR] 2.39, P = 0.008), complicated behavior (penetrating or stricturing) (HR 2.44, P < 0.001) and higher severity indices, at diagnosis, including Harvey–Bradshaw (HR 1.06, P = 0.009) and short Pediatric Crohn's Disease Activity Index (HR 1.02, P = 0.001) were associated with increased risk for intestinal surgery. Age, gender, family history of CD, early introduction of immunomodulators, treatment with anti–tumor necrosis factor α, or diagnosis before the year 2000 did not affect the risk of bowel surgery. Conclusions: Ileal location, complicated behavior, and higher disease activity indices at diagnosis are independent risk factors for bowel surgery, whereas anti–tumor necrosis factor α treatment and diagnosis during the "biological era" are not associated with diminished long-term surgical risk. Abstract : Article first published online 13 October 2016.